PÅ FELTARBEJDE BLANDT FOLK - Wilken, Lisanne (Tidsskriftet Antropologi, 1995)
Lisanne Wilken: Fieldwork among People Personal relationships between the anthropologist and the informants in a given field plays a crucial role for anthropological fieldwork and for the information the anthropologist gets. With reference to personal experiences from fieldwork in Northern and Central Italy, the author argues that methods of establishing and maintaining personal field relations ought to play a much more prominent role in the discussions of anthropological field methods than is usually the case. In today’s discussions of anthropological methodology one can easily get the impression that field relations are coincidentially automatically, established, or that anthropologists have an innate capacity for the creation of social relationships in a variety of social and cultural contexts. The article discusses how dependence on a few close informants may block the collection of data and suggests ways to establish a broad range of informants. One solution is to establish field relations prior to the commencement of fieldwork. This method not only ensures that informants are available when fieldwork is started but also facilitates the cross-cutting of social boundaries which may otherwise be difficult to crosscut.The article also suggests that questionnaires may be used as a method to attract attention to the research project in the field and to broaden the circle of informants. The focus of the article is not the nature of the data collected during fieldwork, but rather the circumstances for the collection of data.